Comparison of Amphotericin B Bladder Irrigations Versus Fluconazole for the Treatment of Candiduria in Intensive Care Unit Patients. (June 2017) - Sullivan, Kelly A.; Caylor, Meghan M.; Lin, Feng-Chang; Campbell-Bright, Stacy
Background: Funguria occurs often in hospitalized patients and is most commonly caused by Candida species. Fluconazole is the agent of choice for most Candida urinary tract infections. Amphotericin B bladder irrigations (ABBI) are an alternative treatment option. Objective: The purpose of this study is to assess the efficacy of ABBI compared to fluconazole for the treatment of candiduria in the intensive care unit (ICU) setting. Methods: We conducted a retrospective chart review of patients admitted to ICUs at our institution with a positive urine culture for Candida species between 2005 and 2012. All patients receiving ABBI were included; patients receiving fluconazole for treatment of candiduria were matched by year. The primary endpoint was achievement of cure. Results: There was no difference in cure between the ABBI and fluconazole groups (59.6% vs. 52.8%, p = 0.55). Clearance was higher in patients receiving ABBI (92.3% vs. 67.9%, p < 0.001). Logistic regression found that renal dysfunction predicted greater cure with ABBI therapy compared to fluconazole (OR 7.63, 95% CI 1.81-32.1). Conclusion: ABBI was equally efficacious in achieving overall cure, and resulted in greater clearance of candiduria compared to fluconazole. ABBI may be considered an alternative to fluconazole for the treatment of candiduria and may be preferred over fluconazole in patients with renal dysfunction.